Quality Control for IG /TR Marker Identification and MRD Analysis - Fronkova, Eva; Svaton, Michael; Trka, Jan (Methods in molecular biology (Clifton, N.J.), 2022)
Selection of the proper target is crucial for clinically relevant monitoring of minimal residual disease (MRD) in patients with acute lymphoblastic leukemia using the quantitation of clonal-specific immunoreceptor (immunoglobulin/T cell receptor) gene rearrangements. Consequently, correct interpretation of the results of the entire analysis is of utmost importance. Here we present an overview of the quality control measures that need to be implemented into the process of marker identification, selection, and subsequent quantitation of the MRD level.
Keywords: Immunoglobulins; PCR; Neoplasm, Residual; Quality control; Precursor Cell Lymphoblastic Leukemia-Lymphoma; lidé; akutní lymfatická leukemie; imunoglobuliny; Next-generation sequencing; biologické markery; Quality Control; reziduální nádor; Biomarkers; Acute lymphoblastic leukemia; Minimal residual disease; řízení kvality; Humans